2018
DOI: 10.5114/jcb.2018.75595
|View full text |Cite
|
Sign up to set email alerts
|

Combined external beam radiotherapy and vaginal brachytherapy versus vaginal brachytherapy in stage I, intermediate- and high-risk cases of endometrium carcinoma

Abstract: PurposeRandomized trials on the effect of external beam radiotherapy (EBRT) with or without vaginal brachytherapy (VBT) for endometrial carcinoma are very few. In view of this, the current study was conducted with the hypothesizes: whether the escalated dose of 26 Gy (VBT alone) in comparison with various major international trials (PORTEC-2) has any difference in rates of disease-free and overall survival with fewer adverse effects in low resource setting like India.Material and methodsAn open-labeled, non-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Nout et al proposed VBT as the first-line adjuvant treatment for patients at intermediate or high risk of developing vaginal recurrence of endometrial and reported fewer gastrointestinal side effects when compared with external beam radiotherapy (EBRT) [18]. The results from a recently reported randomized study showed that VBT treatment alone was as effective as adjuvant EBRT combined with VBT in achieving loco-regional tumor control and resulted in similar survival rates, with fewer episodes of radiation toxicity in patients diagnosed with stage I intermediate-risk and high-risk endometrial carcinoma [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nout et al proposed VBT as the first-line adjuvant treatment for patients at intermediate or high risk of developing vaginal recurrence of endometrial and reported fewer gastrointestinal side effects when compared with external beam radiotherapy (EBRT) [18]. The results from a recently reported randomized study showed that VBT treatment alone was as effective as adjuvant EBRT combined with VBT in achieving loco-regional tumor control and resulted in similar survival rates, with fewer episodes of radiation toxicity in patients diagnosed with stage I intermediate-risk and high-risk endometrial carcinoma [19].…”
Section: Discussionmentioning
confidence: 99%
“…Different data in literature showed one correlation between total dose prescribed, doses for fractions, length of vagina treated, and vaginal late toxicity [8,48,49,50,51,52,53,54,55,56,60,61,62,63,64,65]. Sorbe et al .…”
Section: Discussionmentioning
confidence: 99%
“…Adjuvant brachytherapy provides excellent vaginal control and high survival rates, similar to those after adjuvant EBRT in this intermediate-risk population, as shown in large randomized trials, particularly the PORTEC-2 trial and Swedish trial. [306][307][308][309][310][311][312][313][314] It was also shown that only the small minority of patients with higher risk based on substantial LVSI, p53abn, or L1CAM overexpression had a slightly higher risk of pelvic recurrence with vaginal brachytherapy than those who had EBRT. Therefore, the intermediate-risk category only includes those with none or only focal LVSI and no p53abn.…”
Section: Intermediate Riskmentioning
confidence: 99%